(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This thesis examines the impact of personal income tax (PIT) on economic growth, fiscal stability, and income distribution in five Central Asian countries - Kazakhstan, Uzbekistan, Turkmenistan, Kyrgyzstan, and Tajikistan and three Caucasian countries - Armenia, Georgia, and Azerbaijan. By analyzing specific data over the past decade, this study highlights the nuanced ways in which different PIT policies influence economic outcomes. The thesis concludes with policy recommendations aimed at optimizing PIT structures to support sustainable growth and equity in these regions.